2013
DOI: 10.1149/2.003312ssl
|View full text |Cite
|
Sign up to set email alerts
|

The Deterioration Phenomenon of Amorphous InSnZnO Transistors Derived from the Process of Annealing

Abstract: Thin-film transistors (TFTs) with transparent amorphous indium-tin-zinc-oxide (a-ITZO) channel were fabricated. The field effect mobility (μ) of the a-ITZO TFT was more than 15.0 cm 2 V −1 s −1 , which is higher than the generally reported value of amorphous indium-gallium-zinc-oxide (a-IGZO) TFT. However, μ deteriorated with a decreasing channel length of the a-ITZO TFT due to the annealing process after patterning of the ITZO. We studied the effects of the annealing process on the contact resistance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…In literature, XPS analysis showed that the annealed a-ITZO film has a lower amount of oxygen vacancy. 21 In contrary, for similar type of material (a-IGZO) based TFTs, it is reported that the improved electrical properties at higher anneal temperature suggest a decrease in the density of trap states localized below the conduction band. 3 Overall, we concluded that the a-ITZO film thickness of 8 nm with 30% O 2 content can be considered optimal for further integration.…”
Section: Table I Comparison Of A-itzo Tft Characteristics For Differmentioning
confidence: 97%
“…In literature, XPS analysis showed that the annealed a-ITZO film has a lower amount of oxygen vacancy. 21 In contrary, for similar type of material (a-IGZO) based TFTs, it is reported that the improved electrical properties at higher anneal temperature suggest a decrease in the density of trap states localized below the conduction band. 3 Overall, we concluded that the a-ITZO film thickness of 8 nm with 30% O 2 content can be considered optimal for further integration.…”
Section: Table I Comparison Of A-itzo Tft Characteristics For Differmentioning
confidence: 97%
“…Compared to Device F1, Device F0 (Figure 4B) shows no hysteresis, a comparable V th and SS of −0.8 V and 81.6 mV/decade, a higher on‐off ratio of 1.5 × 10 10 , and improved saturation mobility (μ sat ) of 22.3 cm 2 /Vs. According to Tomai et al, 11 the annealing process before the ESL deposition may result in the generation of a depletion layer under the S/D electrodes and hence the increase of S/D contact resistance. Therefore, the increase of on‐off ratio and mobility in Device F0 can be plausibly explained.…”
Section: Resultsmentioning
confidence: 99%
“…3(a) shows the influence of the PLN process on the transfer curves of Device F1. With the cured F-PI layer, the device exhibits improved electrical characteristics with a positive shift of threshold voltage (Vth) from -3.3 V to -0.7 V, a decrease of subthreshold swing (SS) from 130.2 mV/decade to 80.8 mV/decade, and a rise of on-off ratio from 1.2×10 8 to 4.1×10 9 . The clockwise hysteresis phenomenon observed before the PLN process almost disappears.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to Device F1, Device F0 shows no hysteresis and has a comparable Vth and SS of -0.8 V and 81.6 mV/decade, respectively. Probably due to the elimination of the additional annealing processes [9], the device owns relatively better S/D contacts with no current crowding effect in its output curves (Fig. 3(c)), leading to a higher on-off ratio of 1.5×10 10 and a boosted saturation mobility (µsat) of 22.3 cm 2 /Vs.…”
Section: Resultsmentioning
confidence: 99%